World business leaders interaction in higher education: A novel experience - Gustavo Coronel; Kathleen Mathai (Laureate Education Inc, 2012)
This article describes a disruptive approach that offers higher education students and faculty the experience of learning from world business leaders and interacting with fellow members at their institutions. The World Business Forum event was transmitted live to 36 higher education institutions in 19 countries. Webcast and social media discussions around the event were used to create both a local University community and a global Laureate community. The World Business Forum is a two-day event, produced by HSM Global that serves as a platform for the ideas and trends that are shaping the future of business. In 2011, twenty business and political leaders spoke at the event. Through its partnership with HSM, Laureate was able to broadcast the event to auditoriums on university campuses and to add live content and discussion around speakers, making the webcast relevant to an academic audience. Universities were provided with academic, technical and communication manuals to guide them through the implementation of the event on campus. The network-wide webcast had participation of 36 higher education institutions in 19 countries, and 56,400 viewers. The Laureate- hosted Facebook page generated 2,900 "likes," 3,000 "posts" and 410,000 views and Twitter produced thousands of tweets from around the world. Both the participation on campuses and social media indicated that the webcast provided broad access to the event and created a global forum for students and faculty to participate in the event. DOI: 10.18870/hlrc.v2i1.57